Answers

2014-06-07T15:09:51+08:00
-3 ( 3x + 1 ) = 0     (distribute -3 to 3x + 1)
-9x - 3= 0
-3 = 9x                  (transpose - 9x)
-3/9 = x                 (divide both side by 9)
-1/3 = x                 (reduce to lowest term)

Checking by substitution

-3 ( 3x + 1 ) = 0
-3 ( 3(-1/3) + 1) = 0       (substitute the value of x which is -1/3)
-3 ( -1 + 1 ) = 0
-3 (0) = 0
0 = 0
0
-3(3x+1)
solve for x yan or simplify the equation?
if solve for the value of x then
X = -1/3

if simplify the equation:
-9x - 3
2014-06-07T15:40:19+08:00
-3(3x+1)
=(3)(3x)
=(-3) (1)
=-9 x -3

(by Distributive Property of Multiplication)

Click "Thanks" if I helped. It'll be appreciated. :)
0